1987
DOI: 10.1017/s0025315400026576
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic respiration in the dogfish(Scyliorhinus caniculaL.)

Abstract: Oxygen uptake by dogfish eggs showed an exponential increase with age, reaching a value of around 300 /i\ O 2 h" 1 at 15 °C in eggs about to hatch. Oxygen tensions within the egg-case were fairly steady (25-35 mmHg below ambient) in the case of early stage embryos, but later embryos featured much lower (50-80 mmHg below ambient) and variable oxygen tensions. Dogfish eggs were found to be capable of maintaining high oxygen uptake rates at low ambient oxygen tensions throughout development. They survived long pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…As mentioned, no data on egg fluid pCO 2 and pH is available for other marine organisms; however, judging from the pO 2 versus pCO 2 ratios obtained in our study, in comparison to pO 2 values in-and around eggs or egg masses of other marine animal taxa, it seems likely that many embryos will also be surrounded by fluids of high pCO 2 and low pH: For example, Diez and Davenport (1987) showed that pO 2 values in shark eggs decrease from ca. 18 kPa in early embryos to ca.…”
Section: Perspectivesmentioning
confidence: 61%
“…As mentioned, no data on egg fluid pCO 2 and pH is available for other marine organisms; however, judging from the pO 2 versus pCO 2 ratios obtained in our study, in comparison to pO 2 values in-and around eggs or egg masses of other marine animal taxa, it seems likely that many embryos will also be surrounded by fluids of high pCO 2 and low pH: For example, Diez and Davenport (1987) showed that pO 2 values in shark eggs decrease from ca. 18 kPa in early embryos to ca.…”
Section: Perspectivesmentioning
confidence: 61%
“…embryonic stage) did not influence male ventilation rates or activity patterns. However, since embryonic metabolic demands tend to peak just before hatching [8,46,67,[83][84][85], it is possible that hypoxia impacts embryo survival only towards the end of the brooding period.…”
Section: (C) Paternal Carementioning
confidence: 99%
“…Overall, bamboo shark embryonic development was similar to that of other oviparous elasmobranchs in terms of gross embryo characteristics and respiratory behaviors (Luer and Gilbert 1985;Diez and Davenport 1987;Ballard et al 1993). The major difference between development of bamboo sharks and these other elasmobranchs is that bamboo sharks develop in less than half the time required for temperate species (127 vs. 1300 d, respectively).…”
Section: Discussionmentioning
confidence: 60%
“…Being nourished solely by a maternally supplied yolk, oviparous sharks develop in a fashion superficially similar to embryonic birds and reptiles. However, unlike birds and reptiles, which are amniotes and exchange gases through vascularized extraembryonic membranes, sharks are not amniotes and must, therefore, actively ventilate their egg case at all but the earliest stages of development (Diez and Davenport 1987;Ballard et al 1993;Thomason et al 1996b;Tullis and Peterson 1998;Leonard et al 1999), although additional flow may be generated by external water currents (Koob and Summers 1996). Recently, Leonard and coworkers (1999) demonstrated that ventilatory movements increased the standard metabolic rate of developing skates (Raja erinacea) by approximately 20%.…”
Section: Physiological and Biochemical Zoologymentioning
confidence: 99%
See 1 more Smart Citation